2020
DOI: 10.1002/aic.16920
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the dominant size enlargement mechanism in spray fluidized bed processes

Abstract: This work deals with estimating the dominant size enlargement mechanism in spray fluidized beds. A new process model is presented, which consists of population balances and a heat‐ and mass‐transfer model. New methods to incorporate the wet surface fraction and the Stokes criterion are proposed, which allow for the probability of wet collisions and the probability of successful wet collisions to be calculated. The product of these parameters, the probability of successful collisions, is linked to the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…In a different study, an increasing inlet air temperature leads to a higher evaporation rate of the air and the wet surface fraction decreases from 0.29 at 50°C to 0.01 at 95°C. At low temperatures, the higher surface fraction promotes the agglomerate formation (Rieck, Bück, & Tsotsas, 2020). As the amount of sprayed pure water increased, the collision of wetted particles increased and agglomeration growth advanced (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…In a different study, an increasing inlet air temperature leads to a higher evaporation rate of the air and the wet surface fraction decreases from 0.29 at 50°C to 0.01 at 95°C. At low temperatures, the higher surface fraction promotes the agglomerate formation (Rieck, Bück, & Tsotsas, 2020). As the amount of sprayed pure water increased, the collision of wetted particles increased and agglomeration growth advanced (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Issues of agglomeration and proper coating formation when spraying with polymers can be addressed with optimization experiments of process and formulation parameters 26,40,41 , however, when coating onto seed specifically, it is important to understand the limits of the drying temperature so as to not negatively impact seed germination efficiency. Seeing that desiccation stress was the more detrimental to Cal35, perhaps the ideal conditions for encapsulating similar bacterial inoculants calls for shorter residence times by elevating drying temperatures, similar to the drying conditions seen in spray-drying where survival of Cal35 was greatest.…”
Section: Outlook and Applicationsmentioning
confidence: 99%
“…Due to its excellent mass and heat transfer characteristics, gas–solid fluidized bed technology is widely used in chemical industries and in applications such as drying, combustion, and granulation. , The introduction of forced vibrations of pulsating flow into gas–solid fluidized beds can reduce the bubble size, increase bubble residence times in the bed, increase gas–solid contact efficiency, improve mass and heat transfer efficiency, reduce channel flow and short-circuiting of bed materials, and improve the particle separation efficiency. , Therefore, the use of pulsed fluidized beds is widespread in the fields of drying, combustion, and coal separation. Pence and Beasley , observed increases in the overall heat transfer coefficient from a horizontal cylinder to the bed on the order of 40% for 345 μm particles when a steady secondary flow was added. Dong et al also found that when subjected to a pulsating airflow, the size and number of bubbles in the bed decreased significantly, whereas the motion of the heavy medium became uniform and steady.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent mass and heat transfer characteristics, gas− solid fluidized bed technology is widely used in chemical industries and in applications such as drying, combustion, and granulation. 1,2 The introduction of forced vibrations of pulsating flow into gas−solid fluidized beds can reduce the bubble size, increase bubble residence times in the bed, increase gas−solid contact efficiency, improve mass and heat transfer efficiency, reduce channel flow and short-circuiting of bed materials, and improve the particle separation efficiency. 3,4 Therefore, the use of pulsed fluidized beds is widespread in the fields of drying, combustion, and coal separation.…”
Section: Introductionmentioning
confidence: 99%